Local limit theorems for occupancy models. Issue 1 (27th September 2020) - Barbour, A. D.; Braunsteins, Peter; Ross, Nathan
Abstract : We present a rather general method for proving local limit theorems, with a good rate of convergence, for sums of dependent random variables. The method is applicable when a Stein coupling can be exhibited. Our approach involves both Stein's method for distributional approximation and Stein's method for concentration. As applications, we prove local central limit theorems with rate of convergence for the number of germs with d neighbors in a germ‐grain model, and the number of degree‐ d vertices in an Erdős‐Rényi random graph. In both cases, the error rate is optimal, up to logarithmic factors.